Acoustic characterization of acoustic vases in the synagogue of Tomar, Portugal - António P. O. Carvalho (2020)
This work presents the in situ characterization of the acoustic effect of eight resonant vases, embedded in the walls of the 15th century Synagogue of Tomar (Portugal). The measurement of Reverberation Time (RT) with and without the occlusion of the acoustic vases (achieved by lids of black cork agglomerate coated on the outside with aluminum sheet) showed a very small effectiveness. In global average terms (all frequencies, all points' average), the room's RT changed from 4.89 s (closed vases) to 4.80 s (open vases) in an empty room (overall reduction of 1.4%). Per 1/3 octave frequency band, a small reduction in the reverberation time values was found in almost all frequency bands (except 160, 500, 1250, 2000, 3150 and 5000 Hz). The biggest RT reductions were in the 125 and 250 Hz bands (about 0.5 s or 9%). The acoustic resonance frequency in those cavity resonators was found between 100 and 200 Hz.